Mathematical Reasoning: An Analysis Of Madrasah Ibtidaiyah Teacher Education (PGMI) Novice Teachers' Abilities - Utami, Ratna Widianti; Alawiyah, Arsyiatul; Waritsman, Arsyil (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2025)
Mathematical reasoning is the process of drawing conclusions about a number of ideas based on existing facts when solving Mathematical problems. This reasoning ability is one of the abilities that must be possessed when learning Mathematics. Given the importance of reasoning ability, prospective teachers are expected to have the ability to develop their own Mathematical reasoning. The research aims to analyze the athematical reasoning ability of Madrasah Ibtidaiyah Teacher Education (PGMI) novice teachers' abilities at STAI Putra Galuh Ciamis. The type of research used is mixed method. The subjects in the research were 21 novice teachers' from the Madrasah Ibtidaiyah Teacher Education study program. Subjects were taken using the purposive sampling technique. Data analysis techniques include data reduction, data presentation, data interpretation, and conclusion drawing. The research provides results showing that as many as 58% of novice teachers'[1]are still in the very low category in their Mathematical reasoning skills. Mathematical reasoning ability on indicators of analyzing Mathematical situations has an average of 69% in the moderate category, then on indicators of planning the solution process 63% in the moderate category, solving problems with systematic steps 57% in the low category, and drawing logical conclusions 50% in the very low category